Determination of urinary coenzyme Q10 by HPLC with electrochemical detection: Reference values for a paediatric population. (19th November 2015) - Yubero, Dèlia; Montero, Raquel; Ramos, Maria; Neergheen, Viruna; Navas, Plácido; Artuch, Rafael; Hargreaves, Iain
Abstract: Kidney dysfunction is being increasingly associated with mitochondrial diseases and coenzyme Q10 (CoQ) deficiency. The assessment of CoQ status requires the biochemical determination of CoQ in biological fluids and different cell types, but no methods have been developed as yet for the analysis of CoQ in excretory systems. The aim of this study was to standardize a new procedure for urinary CoQ determination and to establish reference values for a paediatric population. Urinary CoQ was analyzed by HPLC with electrochemical detection. Reference values ( n = 43) were stratified into two age groups (2–10 years: range 24–109 nmol CoQ/gram of pellet protein; 11–17 years: range 43–139 nmol CoQ/gram of pellet protein). In conclusion, urinary CoQ analysis is a noninvasive, reliable, and reproducible method to determine urinary tract CoQ status. © 2015 BioFactors, 41(6):424–430, 2015